SOCIAL CONTROL THROUGH ACCOUNTS. - Robem, C. Rufus (The Accounting Review, 1928)
Abstract This article deals with some applications of accounting as a tool for social control of economic activity, as opposed to the internal administrative control of a particular business. It is the purpose rather to bring together some facts with which most accountants are familiar, but which have not usually been discussed as presenting similar problems. various aspects of social control through accounts will be set forth under following heads, accounting as a tool for controlling governmental activities, the administration by a government of duties which are primarily economic in nature, accounting for non-profit institutions, governmental uses of accounting to control private enterprises, both public utilities and those enterprises which are not so commonly recognized as being of a public or quasi-public nature, uses of accounting by groups of private enterprises in an attempt to co-ordinate their activities and to increase their individual efficiency, the profession of public accountancy which has developed in the modern economic order. Private enterprises attempt to earn the greatest possible income with the least possible expense, the amount by which income exceeds expense is the measure of the success of a private enterprise. A government, on the other hand, attempts merely to collect sufficient income to cover an agreed expense program over a given period of time.